CARBON ACCOUNTING, DISCLOSURE AND MEASUREEMENT: A Systematic Literature Review - Saraswati, Erwin (Accounting Department,, 2020)
ABSTRACTPurpose — This research aims to support Sustainable Development Goals specifically to reduce carbon emission. Design/methodology/approach — Systematical literature review was used as a research method, evaluated and analyzed as much as 17 articles.Findings — The result indicate that mitigation is more preferable than adaptation in case of carbon emission accounting definition. Stakeholders were involved to applied carbon disclosure which support the stakeholder theory, while measurement of carbon emission found that carbon-footprint approach is more widely used by organizations.Practical Implications — Environmental field become one of the SDG’s (Sustainable Development Goals) objectiveas it is related to the climate change caused by carbon emission that significantly increase from 1990’s.Originality/value — This research delivers concept, definition, practice, and measurement of gas emission based on previous research result (by several researchers/research paper) in various countries.Keywords — Climate change, carbon accounting, adaptationandmitigation, carbon-footprint approach.